Virgin coconut oil dielectrical properties as electrical insulation material - Siti Syafiqah Mat Sauki; Nor Asiah Muhamad; Zawani Amirah Rasid (Institute of Advanced Engineering and Science, 2019)
Mineral oil played an important role as insulating liquid such as to reduce failure, ageing effect, increase the life span and heat transfer agent. Mineral oil had a good dielectric strength and cooling performance but it had serious negative environmental impact like non-biodegradable, non-renewable resource and difficult to dispose when it deteriorates completely. Hence, virgin coconut oil (VCO) was chosen as alternative to replace mineral oil since it biodegrades completely without toxic and easy to get in the tropical country. Three dielectric tests were conducted to investigate the dielectric properties of VCO. Those were breakdown voltage, water content and kinematic viscosity. A study about the effect of the moisture level of VCO on the breakdown voltage and kinematic viscosity was also presented. VCO and mineral oil also undergone heating process to reduce moisture in sample. The study showed that VCO has good potential breakdown voltage with the ability to absorb a lot of moisture keeping the KRAFT paper dry. However, VCO had very high kinematic viscosity compared to mineral oil. Further, the rate of breakdown voltage decreases with increasing of moisture of VCO was lower than mineral oil.